1839 Ky. Acts 246, An Act to Amend the Several Acts Concerning the Towns of Paris and Elizabethtown, chap. 1279, § 8. - (:unkn) unknown (General Publisher, 1839)
They shall have power to ordain a penalty on persons who shall be guilty of running horses within the limits of said town, blowing horns, or crying aloud, in such manner as to disturb the peace and quiet of the town, or the shooting a gun, or pistol in said town, any sum not exceeding twenty dollars.
--
Keywords: DISCHARGE